Analysis Of Counsel Support With The Time Of Disclosure Of Personal Status Of People with HIV/AIDS (ODHA) Against His Partners In Sumenep District - Dian Permatasari; Eva Nurhidayati; Dian Ika Puspitasari (Universitas STRADA Indonesia, 2020)
Human Immunodeficiency Virus and Acquired Immuno Deficiency Syndrome have become epidemics that seriously of the world community. East Java is one of the provinces with the highest number of HIV / AIDS sufferers in Indonesia. As of September 2018, the number of people living with HIV / AIDS was 47,396 people. This research is a quantitative research design with explanatory research which aims at research conducted to explain the influence between independent and dependent variables through testing. Cross sectional design because the independent and dependent variables were measured at the same time. The sampling technique used total sampling. The instrument in this study was a questionnaire. Data were analyzed using regression test. One of the solutions to overcome this problem is the role of peer support groups in providing support and services to ODHA by providing access to information and referrals about treatment.